The financing of the community after the Edinburgh European Council - Peter Zangl (Intereconomics, 1993)
At its Edinburgh meeting on 11th and 12th December 1992 the European Council came to a number of conclusions regarding the future financing of the Community. The following article examines the implications of the new financial perspective.
Keywords: 330; European Community